Islamic Mysticism of Wali Songo - Muhajirin, Muhajirin; Mahmuddin; Santalia, Indo; Nafis, Andi Ahmad Zahri (LPPM IAIN Sultan Amai Gorontalo, 2025)
This research explores the mystical dimension in the da'wah (Islamic missionary) strategy of Wali Songo, a group of prominent Islamic figures in the history of Islamization in Java. The study investigates how Sufi elements and mysticism were integrated into cultural expressions to support the dissemination of Islamic teachings. The research was motivated by the need to understand the success of Wali Songo's inclusive approach, especially in engaging local belief systems and cultural traditions. This study employed a qualitative approach using descriptive-analytical methods. Data were collected from classical texts, folklore, and previous research on Wali Songo. The findings show that Wali Songo's da'wah extensively adopted Sufi practices such as dhikr, wirid, and the use of spiritual symbols. They reinterpreted local cultural expressions—like wayang performances, gamelan, and traditional ceremonies—as Islamic mediums. The cultural accommodation strategy, especially by figures such as Sunan Kalijaga, reveals a sophisticated understanding of local wisdom and the effective contextualization of Islamic teachings.